2004
DOI: 10.1063/1.1771502
|View full text |Cite
|
Sign up to set email alerts
|

Performance summary on a high power dense plasma focus x-ray lithography point source producing 70 nm line features in AlGaAs microcircuits

Abstract: A high average power dense plasma focus (DPF), x-ray point source has been used to produce ∼70 nm line features in AlGaAs-based monolithic millimeter-wave integrated circuits (MMICs). The DPF source has produced up to 12 J per pulse of x-ray energy into 4π steradians at ∼1 keV effective wavelength in ∼2 Torr neon at pulse repetition rates up to 60 Hz, with an effective x-ray yield efficiency of ∼0.8%. Plasma temperature and electron concentration are estimated from the x-ray spectrum to be ∼170 eV and ∼5·1019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Ion beams of desired gas are generally used for surface treatments [8,9] as well as neutron beams for neutronic detection of hydrogen in samples [10,11] and lithography by means of electron beams [12,13]. X-rays, in particular, have extensive applications such as X-ray microscopy, X-ray lithography, micromachining, radiography, and material synthesis [14][15][16][17][18][19][20][21]. Radiography of the biological samples and X-ray imaging of moving metallic objects are two of the most noticeable applications of radiated hard X-ray in PF devices.…”
Section: Introductionmentioning
confidence: 99%
“…Ion beams of desired gas are generally used for surface treatments [8,9] as well as neutron beams for neutronic detection of hydrogen in samples [10,11] and lithography by means of electron beams [12,13]. X-rays, in particular, have extensive applications such as X-ray microscopy, X-ray lithography, micromachining, radiography, and material synthesis [14][15][16][17][18][19][20][21]. Radiography of the biological samples and X-ray imaging of moving metallic objects are two of the most noticeable applications of radiated hard X-ray in PF devices.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Petr et al reported a 40% standard deviation in Neon K-shell yield so a 61% variation in neutron yield does not seem unreasonable considering that the DD fusion reaction relies on nonthermal processes, while the K-shell production relies on thermal physics with some contribution of non-thermal physics. 3 A key point is to compare the neutron yield from the transformer-based plasma focus with a conventional plasma focus pulse power system. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Petr et al demonstrated a solid state switched plasma focus system that operated for 10 7 pulses in Ne for lithography applications. 3 Many of the perceived problems of pulse power driven radiation sources were addressed including reliable pulse power, electrode lifetime and insulator lifetime. The working gas flowed, which maintained a fresh supply of gas in the chamber.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma focus (PF) is among the low-priced available neutron and ions generators, with unique features of extremely short pulses (hundreds of ns) that suit it for different interesting applications [3][4][5][6]. Similarly, the soft X-rays emitted from PF have attracted the many researchers due to large numbers of application such as high brightness source for lithography in order to fabricate the electronic devices, X-ray laser pumping, X-ray Microscopy, X-ray backlighting and radiography [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%